Infection control awareness amongst illiterate workers in an Indian intensive care unit: Impact of an unconventional educational intervention - Singh, Parikshit; Baronia, Arvind; Prasad, KN; Dhole, TN; Singh, SK (International Journal of Infection Control, 2011)
Illiterate workers, with very poor infection control awareness, abound the ICUs of developing nations resulting in difficulties in controlling Hospital Acquired Infections (HAI). The illiterate ICU workers were exposed to verbal-visual educational intervention by a microbiology laboratory visit and the HAI related awareness levels assessed by a pre and post-visit questionnaire. Intervention caused significant improvement in awareness and attitude proving that visual methods of teaching infection control suits illiterate workers better than conventional methods.